2022
DOI: 10.1093/ejcts/ezac248
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment prediction of tumour spread through air spaces in clinical stage I non-small-cell lung cancer

Abstract: Objectives To construct a nomogram prediction model for tumour spread through air spaces (STAS) in clinical stage I non-small cell lung cancer (NSCLC) and discuss its potential application value. Methods 380 patients with clinical stage I NSCLC in Tianjin Chest Hospital were collected as the training cohort and 285 patients in Fujian Provincial Hospital were collected as the validation cohort. Univariable and multivariable lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Furthermore, 95% (152/160) of the STAS patients had a CTR value greater than 0.5, and the results were consistent with the study by Ding and colleagues. 11 Moreover, a definite correlation between the Rad‐score and CTR was observed, with a Wilcoxon test p‐ value < 0.01, which suggested a discernible association between STAS and CTR.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Furthermore, 95% (152/160) of the STAS patients had a CTR value greater than 0.5, and the results were consistent with the study by Ding and colleagues. 11 Moreover, a definite correlation between the Rad‐score and CTR was observed, with a Wilcoxon test p‐ value < 0.01, which suggested a discernible association between STAS and CTR.…”
Section: Discussionmentioning
confidence: 90%
“…Due to the prevalent utilization of thin‐section computed tomography (CT) and the increased detection rate of early‐stage NSCLC, 8 STAS has gradually become known and understood in academia. Several previous studies have reported that STAS usually presents as solid or subsolid nodules in CT images and is correlated with factors such as maximum tumor diameters (Tdmax), solid component diameters, and consolidation tumor ratio (CTR) 9–11 . Nevertheless, the interpretation of CT images relies highly on the diagnostic experience of doctors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies that aimed to create a prediction model using radiomic values, it was suggested that those values can guide the preoperative prediction of STAS in early stage lung adenocarcinoma and related surgeries [10]. In fact, there was a study that stated there was good calibration in the nomogram prediction model of STAS in clinical Stage I non-small cell lung cancer (NSCLC) [11]. However, these studies were retrospective, which can lead to selection bias, and they were conducted in a limited number of centers and with a limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the sublobar resection group but not in the lobectomy group, Eguchi et al discovered that the risk for recurrence of STAS-positive NSCLC patients was considerably higher than that of STAS-negative patients [12]. Several strategies are currently being used for the preoperative prediction of STAS, including CT-based radiomics, intraoperative frozen section assessment, and nomogram prediction models based on clinical factors [13][14][15][16]. However, due to the limited predictive e cacy and low widespread clinical application, preoperative STAS prediction remains challenging and should be further developed in a larger context.Peripheral blood indexes have exhibited an increasingly promising role in predicting the prognosis and evaluating the e cacy of antitumour treatment.…”
mentioning
confidence: 99%